Multiple bilateral impacted distomolars in nonsyndromic condition: A rare case report - Amirhossein Moaddabi; Mohammad Hassan Samandari; Mohammad Javad Shirani; Parisa Soltani (Wolters Kluwer Medknow Publications, 2015)
The presence of multiple supernumerary teeth in nonsyndromic patients is uncommon. In these patients, the prevalence of extra teeth in the molar regions of both jaws is rare. This study aimed to present a rare case of a 27-year-old woman, with nonsyndromic multiple distomolar supernumerary teeth causing vague and diffuse pain in periauricular, temporomandibular joint, and temporal regions. Impacted third molar and distomolar that were in a close contact with inferior alveolar nerve canal were extracted with minimum bone removal.